The Concept of Maşlaḥah Family in Lampung Customary Law: A Study of Mak Dijuk Siang and Its Relevance to Indonesian Marriage Law - Habib Shulton Asnawi; M. Anwar Nawawi; Siti Mahmudah; Alamsyah Alamsyah (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
This article discusses the concept of maşlaḥah family, which is part of the customary law of Mak Dijuk Siang (prohibition of divorce) in the Lampung Pepadun Megou Pak clan. Despite the prohibition of divorce, household problems are addressed within the community, and there are customary sanctions for violating this rule. The purpose of this article is to analyze why traditional leaders enforce and uphold the Mak Dijuk Siang customary rules and their relevance to Indonesian marriage law. The study uses a qualitative method, combining field research with library research in the sociology of law. The research was conducted in the Lampung Pepadun Megou Pak community in Tulang Bawang Regency and West Tulang Bawang Regency, Lampung Province. Primary data was obtained from traditional leaders through observation, interviews, and documentation. The analysis applies the theory of legal effectiveness. The results show that the concept of maşlaḥah family in the Mak Dijuk Siang rule reflects the community's belief in the philosophy of Piil Pesenggiri, which discourages divorce and aims to build eternal families. In cases of household conflicts, mediation is preferred through the Penyimbang Pepung Adat Customary Institution. The practice of maşlaḥah family through the Mak Dijuk Siang customary rules has been effective in reducing the high divorce rate, demonstrating its relevance to Indonesian marriage law.